2017
DOI: 10.4081/jphr.2017.815
|View full text |Cite
|
Sign up to set email alerts
|

Social Marketing for a Farmer's Market in an Underserved Community: A Needs Assessment

Abstract: The aim of the present paper is to assess local residents’ awareness of utilizing Supplemental Nutrition Assistance Program (SNAP) benefits to purchase fresh produce at local farmers’ markets, and to determine internet use and media preferences of study participants prior to implementation of a social marketing campaign. A needs assessment was conducted to collect baseline data in an underserved neighbourhood in New Orleans (La, USA). The study was carried out August 2014-May 2015. The assessment revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…Nevertheless, more than a third of the customers at people-of-color-operated farmers markets are people of color. This finding is noteworthy as earlier studies have found that low numbers of people of color visit and shop at farmers markets (Nuss et al, 2017; Singleton et al, 2020; Skizim et al, 2017).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Nevertheless, more than a third of the customers at people-of-color-operated farmers markets are people of color. This finding is noteworthy as earlier studies have found that low numbers of people of color visit and shop at farmers markets (Nuss et al, 2017; Singleton et al, 2020; Skizim et al, 2017).…”
Section: Discussionsupporting
confidence: 57%
“…The study found that 88% of the respondents shopped for fruits and vegetables at grocery stores and 84% obtained these items at Walmart ( Nuss et al, 2017 ). Skizim et al (2017) found that 63% of low-income New Orleans residents never visited a farmers market, while 27% of middle- and high-income residents never went to farmers market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The positive impact of both social media usage and informal marketing may suggest that social media, word-of-mouth and environmental print could be effective ways to promote EBT sales at farmers' markets. Other studies have found that environmental print is more effective than newspaper advertising for reaching low-income audiences with health messaging and that internet-based advertising and social media are increasingly viable methods for reaching low-income populations (47,48) . Future studies might assess whether this type of outreach is associated with a greater sense of community connectedness with the market; particularly given that in the current study the impact of socialmedia-based outreach appeared greater than the impact of price (double-bucks promotions) on sales.…”
Section: Discussionmentioning
confidence: 99%